(untitled) (Al-Academy, 2021)
The operative system of theatrical performance depends on the construction of the scenographic space, as it constitutes the most aesthetic effect of the recipient, and the body of the theatrical discourse that contains the signs of the show, and it comes as an embodiment of the directing vision of the show director, so most of the world directors resorted to attention to the output treatment to establish the scenographic space, and thus it possesses a contrast in The embodiment of the directing vision according to the stylistic and hermeneutical dimension of the director, so the two researchers found the importance of studying the topic, and the study came under the title (Directing Treatments of the Scenographic Space in the Iraqi Theatrical Show - Shakespeare Texts as a Model) , so the research included the introduction and it included the research problem and it answers the following question: How did the director treat Theatrical scenography in Shakespearean texts?, And the importance of the research and the goal of the research that aims to reveal the stylistic aesthetics in the making of the scenographic space of the Shakespearean text externally, as well as included the boundaries of research and defining terms, and then the research contained two topics, the first topic came under the title of the semantic employment of scenography in the theatrical presentation As for the second topic, titled Aesthetic Work of Scenography in Theatrical Experiments International, and then the research procedures and sample analysis, and the sample was from two theatrical performances, namely (Macbeth) written by William Shakespeare and directed by Salah the Reed and the second (The Blood Horse) prepared and directed by Jabbar Judy, which is prepared on several Shakespeare plays, and the results of the research came, the most prominent of which are: The directing vision was based on the lived reality For the recipient in establishing the aesthetic system of the presentation came in the sample (Macbeth) on the philosophical space that formed the dominant reality over the recipient, as well as in the performance of the play (Blood Horse) that political reality dominated the construction of the scenographic space in the show, and the research concluded with a list of sources